Additive Manufacturing in Prosthetics Field: A Literature Review - Ginting, Rosnani; Ishak, Aulia; Nasution, Fadylla Ramadhani Putri; Malik, Alfin Fauzi; Bangun, Putri Syahmina Atirah (Jurnal Sistem Teknik Industri, 2025)
Prosthetic devices play a critical role in restoring mobility and enhancing the quality of life for individuals who have experienced limb loss due to trauma, disease, or congenital conditions. However, the high cost, discomfort, and limited accessibility of conventional prosthetics present ongoing challenges. In response, Additive Manufacturing (AM), particularly 3D printing, has emerged as a transformative solution in the field of prosthetics. This technology enables the creation of patient-specific prosthetic components with complex geometries, improved fit, and reduced weight, all while lowering production costs and minimizing the need for post-processing. Through a comprehensive review of recent studies, this paper explores the advancements and applications of AM in prosthetics, including the integration of machine learning, finite element method (FEM) simulations, and new materials such as PLA, ABS, ASA, and carbon fiber-reinforced composites. Research findings indicate that AM facilitates the development of durable, lightweight, and anatomically accurate devices, such as transfemoral sockets and prosthetic thumbs, which pass international fatigue and safety standards. The studies also highlight the advantages of AM in pediatric prosthetic design, where rapid anatomical changes necessitate frequent adjustments. By streamlining the production process and enabling customization, AM significantly improves comfort, usability, and accessibility for users. This review concludes that additive manufacturing holds immense potential to revolutionize prosthetic development by offering cost-effective, sustainable, and user-centered solutions. The continued advancement and integration of digital manufacturing technologies are poised to address existing limitations in prosthetic care and support the growing global demand for innovative, inclusive, and high-quality assistive devices.